Pengembangan Soal Numerasi Model PISA untuk Meningkatkan Kompetensi Siswa - Hari Sugiharto Setyaedhi (Jurnal Pendidikan Indonesia, 2025)
The Program for International Student Assessment (PISA) test shows that the mathematics achievement of Indonesian students is very low. The solution is to develop PISA-model numeracy questions. This research is a development research type, aiming to design and develop appropriate PISA model numeracy questions in high schools. Data collection techniques were obtained through observation, interviews, and questionnaires. The data were analyzed using quantitative descriptive methods. The development model uses formative evaluation (self-evaluation, expert reviews, one-to-one, and small group). The research subjects consisted of educational evaluation experts and used 15 high school students as research subjects: 3 students at the one-to-one stage and 12 students at the small group stage. The results of the research produced a product in the form of 25 PISA model numeracy questions and were declared feasible as follows: a) The material evaluation validation results were 91% (very feasible), test construction 93% (very feasible), and language 91% (very feasible category), individual trials 82% (very feasible), and small group trials 86% (very feasible). The conclusion of research on the development of HOTS-integrated AKM questions is that they are very suitable to be used as a test tool. The implications of the results of this research regarding PISA model numeracy can improve student competence in high school.